Infectious Etiology of Hospitalized CommunityAcquired Pneumonia Patients in Turkey - Hakan ERDEM (Flora Infeksiyon Hastalıkları ve Klinik Mikrobiyoloji Dergisi, 2009)
This paper aims to evaluate the causative agents in patients hospitalized due to community-acquired pneumonia in Turkey. Fourteen local studies are assessed and pneumococci are the main etiological agents followed by enteric gram-negative bacilli, streptococci other than pneumococci, Staphylococcus aureus and Haemophilus influenzae. On the other hand, Mycoplasma species are the leading etiological agents preceeding Chlamydia and Legionella in atypical pneumonia that comprise 29% of community-acquired pneumonia in Turkey.